Explaining the Influence of the Observer on Quantum Measurements and the Influence of Sick Patients on the Doctor (Global Journal of Science Frontier Research, 2022)
The article explains for the first time the influence of the observer on quantum measurements. 1/ In one set of experiments, it was found that the lifetime of decay of radioactive elements is longer in the presence of spinning liquids or solids. This could only be explained if media between them was present, which was influenced by the spinning. 2/ In another set of experiments, it was found that the lifetime of decay of radioactive elements is longer in the presence of people. Since the Russian scientist Shkatov developed equipment allowing him to measure the spinning of the human's aura, the longer lifetime of radioactive elements in the presence of people could be explained with the influence of their spinning aura (but again the influence could only be explained with the presence of media, which was influenced by the spinning). 3/ In another set of experiments, it was found that without the presence of observer photons and electrons behaved like waves and diffraction pattern was observed when they were passing through two slits. When observer with his spinning aura was present, the photons and electrons behave like particles -diffraction was not observed but only two slits of light. This means that under the influence of observers' spinning aura the photons and electrons behave like particles, which could only be explained if there was a media influenced by the spinning aura of the observer.
Keywords: spinning influence on quantum measurements; observers’ influence on quantum measurements